Determining actors in adolescents adherence to treatment in a Psychosocial Care Center (CAPS AD): A theoretical reflection (Research, Society and Development, 2024)
This article seeks to understand, through bibliographical research the factors that influence adolescents' adherence to the treatment offered by a CAPS AD. With the increase in the use of psychoactive substances among adolescents in Brazil, the study highlights the importance of understanding this phase and the factors that influence early drug use. CAPS AD is part of the Psychosocial Care Network (RAPS), which serves people who use alcohol and other drugs, offering an alternative treatment to traditional hospitalization, with a focus on social and family reintegration. Adolescence is marked by physical, psychological and social changes, as a result of which adolescents become more vulnerable to substance use, being influenced by curiosity, the search for identity and family influences. Treatment at CAPS AD prioritizes socialization and creating bonds, proving to be more effective than hospitalization, specifically for adolescents. Participation in therapeutic workshops and recreational activities facilitates adherence to treatment along with the formation of bonds with other adolescents and the health team. Family support proved to be crucial for successful treatment. Adherence to treatment is influenced by individual and external factors, specifically such as family support and the mental health team, which strengthen bonds and guarantee commitment to the adolescent. Despite advances following psychiatric reform, CAPS AD face challenges due to lack of financial resources.